Genesis of interictal spikes in the CA1: a computational investigation - Ratnadurai Giridharan, Shivakeshavan; Stefanescu, Roxana A.; Khargonekar, Pramod P.; Carney, Paul R.; Talathi, Sachin S. (Frontiers in Neural Circuits, 2014)
Interictal spikes (IISs) are spontaneous high amplitude, short time duration (< 400 ms) events often observed in EEG of epileptic patients. In this paper, we develop a biophysically relevant network model of the CA1 subfield and investigate how changes in the network properties influence the susceptibility of CA1 to exhibit IISs. We present a novel template based approach to identify conditions under which synchronization of paroxysmal depolarization shift (PDS) events evoked in CA1 pyramidal (Py) cells can trigger an IIS. We use the results of this analysis to develop a detailed network model of the CA1 subfield in order to address the following questions: 1) How does IIS formation depend on the degree of sprouting (recurrent connections) between the CA1 Py cells, and the fraction of CA3 Shaffer collateral (SC) connections onto the CA1 Py cells? and 2) Is synchronous afferent input from the SC essential for the CA1 to exhibit IIS? We demonstrate that the CA1 subfield with low recurrent connectivity (absence of sprouting; normal brain) has a low probability of producing an IIS except when a large fraction of CA1 neurons (>80%) receives a barrage of quasi-synchronous afferent input via the SC. However, as we increase the recurrent connectivity of the CA1 (>40%); mimicking sprouting in a pathological CA1 network), the CA1 can exhibit IIS even in the absence of a barrage of quasi-synchronous afferents from the SC (input occurring within temporal window $>$80 ms) and a low fraction of CA1 Py cells (approximately 30%) receiving SC input. We also find that in the presence of Poisson distributed random (asynchronous) input via SC, the CA1 network generates spontaneous periodic IISs (approximately 3 Hz) for high degrees of recurrent Py connectivity (>70%). Our investigations find that spontaneous IISs closely depend on the degree of the network's intrinsic excitability.